A new spectrophotometric method for the determination of Baygon in environment and biological samples - Patel, V; Rai, M K; Rai, J K (Recent Research in Science and Technology, 2013)
A sensitive, selective, cheaper and extractive spectrophotometeric method has been developed for the detection and determination of Baygon in fruits, vegetables, and grains is based on the coupling of their hydrolysation products with diazotized aniline. The dyes formed are measured at 450nm for Baygon after extraction in chloroform. Beer’s law is obeyed over concentration ranges of 0.8-5.0µg. The Molar absorptivity and Sandell’s sensitivity were found to be 9.7×105 L mol-1 cm-1 and 0.5×10-4 µg cm-2 respectively. The standard deviation and relative standard deviation were observed as ± 0.00336 and 0.0145% respectively. Various important analytical parameters were evaluated. The method was applied successfully to the determination of Baygon in water, grain, fruits, plant material and biological sample.